Assessment of the effects of seasonality on the ecotoxicity induced by the particulate matter using the animal model Caenorhabditis elegans. (March 2022) - Cáceres Quijano, Maria Fernanda; de Paula Ribeiro, Joaquim; Josende, Marcelo Estrella; Santa-Helena, Eduarda; De Falco, Anna; Gioda, Carolina Rosa; Gioda, Adriana
Abstract: The present work aimed to establish potential changes in the ecotoxicological effects on C. elegans induced by the exposure of coarse (PM10 ) and fine (PM2.5 ) particulate matter collected during dry and rainy periods. We also analyzed the probable influence on the change of a city's activities as the mega-events result in air quality. The element levels evaluation was performed on PM, on the solutions of exposure, and C. elegans after exposure. Biochemical essays were performed to evaluate damage to C. elegans . The results showed that infrastructure works increased the levels of pollutants, generating increases in the concentrations of PM2.5 and PM10 . The biochemical results suggested effects mediated by different mechanisms, where PM2.5 induced an increase in antioxidant capacity with activation of the defense system and lipoperoxidation. Results suggest that PM10 reduces the antioxidant capacity and activates the glutathione S-transferase activity enzymatic action, but also induces lipoperoxidation in all groups of animals exposed to samples collected during the dry period of 2016. Individuals exposed to PM2.5 in 2017 wet and dry periods and PM10 in 2016 and 2017 dry periods shown a decrease in size compared to controls, while for fertility data, there was a decrease only in individuals exposed to PM2.5 in the periods that the highest levels of PM concentration. We conclude that despite the positive issues linked to the hosting of mega-events, their infrastructure requirements can compromise air quality and bring damage related to lipoperoxidation and physiological changes in the life cycle of biological systems, such as what happened to C. elegans exposed to tested extracts. Also, rainy events reduced the presence of these pollutants, washing the atmosphere. Graphical abstract: Image 1 Highlights: Establish changes on C. elegans induced by the exposure particulate matter. PM2.5 induced an increase in antioxidant capacity. PM10 reduces the antioxidant capacity. Exposure shown a decrease in size compared to controls. Fertility decreases in individuals exposed to the highest levels of PM.